Analyzing the Perceptions and Expectations of Students Towards Science Using Soft System Methodology - Firmansyah, Juli; Ibrahim, Ibrahim; Saputra, Hendri (Jurnal Pendidikan Progresif, 2024)
Abstract: Analyzing the Perceptions and Expectations of Students Toward Science Using Soft System Methodology. Objectives: This research aims to analyze students’ perceptions and expectations regarding science lessons so that the resulting data and information can be utilized by teachers as learning leaders to be applied in the learning process. Methods: A soft system methodology (SSM) approach was used to achieve this goal. With SSM, this problem can be overcome. SSM produces a conceptual model to formulate a strategy for Aceh junior high school science teachers. The observation locations were conducted at ten junior high schools (SMP) in two districts in Aceh. Findings: Several factors influence students' interest in learning science, namely learning facilities in representative classrooms and laboratories, availability of resources, media and learning facilities, and teaching materials with virtual support. Several other factors were also found in different schools, such as the low ability of teachers to manage classes, not yet optimal preparation for learning and practicums, not all science teachers utilizing laboratories, and the unavailability of virtual laboratories. Conclusion: The results of the SSM method analysis produced two suggested recommendations. The first is a technical recommendation, namely that teachers must make efforts to improve the quality and services of learning, such as trying to take advantage of the unique learning environment to support education and providing exciting learning materials, resources, and facilities as a result of continuously improving professional performance. Second, policy recommendations such as determining appropriate learning models and strategies and choosing practicum models and approaches that can equip students with knowledge, skills, and attitudes toward students. Keywords: science lessons, science teachers, soft systems methodology, student interests.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202433